Analisis Semantik Terjemahan Alquran Surah Al Waqiah - Andriani, Sulihin Azis (Celebes Education Review, 2019)
Abstract. The meaning of the translation of the Qur'an in Islam has begun since the Qur'an itself was revealed. This tradition of meaning is one of the efforts that is expected to find the intrinsic meanings contained in the Qur'an which is the word of God. One such effort is with semantic analysis, an approach related to the meaning of the expression of a language. This study aims to describe the semantic analysis of the translation of the Qur'an Surah Al Waqiah verses 1-44 on the Al Mishbah interpretation. To achieve these objectives data on the meaning contained in the translation of the Qur'an Surah Al Waqiah verses 1-44 on the Al Mishbah interpretation by using note and document techniques. The results of the study obtained were Surah Al Waqiah discussing the Day of Resurrection, as the meaning of the word Al Waqiah is the Day of Resurrection. In surah Al Waqiah verses 1-44 explain about the events that occurred on the Day of Judgment that happened. Humans will be divided into three groups; the right, the left, and those who have blessed first. Those who belong to the right and who get mercy beforehand will be placed in heaven and get invaluable pleasure, while those belonging to the left will be placed in hell and will be rewarded for their actions while living on earth Abstrak. Pemaknaan terhadap terjemahan Alquran dalam Islam sudah dimulai semenjak Alquran itu sendiri diturunkan. Tradisi pemaknaan ini salah satu upaya yang diharapkan akan menemukan makna-makna hakiki yang terdapat dalam Alquran yang merupakan kalam Allah. Salah satu upaya tersebut ialah dengan analisis semantik, pendekatan yang berhubungan dengan makna dari ungkapan suatu bahasa. Penelitian ini bertujuan untuk mendeskripsikan analisis semantik terjemahan Alquran Surah Al Waqiah ayat 1-44 pada Tafsir Al Mishbah. Untuk mencapai tujuan tersebut dikumpulkan data tentang makna yang terkandung dalam terjemahan Alquran Surah Al Waqiah ayat 1-44 pada Tafsir Al Mishbah dengan menggunakan teknik simak catat dan dokumen. Hasil penelitian yang diperoleh adalah surah Al Waqiah membahas mengenai hari kiamat, sebagaimana arti dari kata Al Waqiah yaitu hari kiamat. Dalam surah Al Waqiah ayat 1-44 menjelaskan tentang kejadian-kejadian yang terjadi pada saat hari kiamat itu terjadi. Manusia akan dibagi menjadi tiga golongan; golongan kanan, kiri, dan orang-orang yang telah mandapat rahmat terlebih dahulu. Mereka yang termasuk dalam golongan kanan dan yang mendapat rahmat terlebih dahulu akan ditempatkan di surga dan mendapatkan kenikmatan yang tidak ternilai, sementara mereka yang termasuk golongan kiri akan ditempatkan di neraka dan akan mendapat balasan perbuatannya selama hidup di dunia.